Premarital sex and pregnancy in Greater Jakarta - James O’Donnell; Iwu Dwisetyani Utomo; Peter McDonald (Genus, 2020)
Abstract Social taboos and stigmas around sexuality and non-marital sex in Indonesia have led to substantial underreporting of the prevalence of premarital sex. In this study, we explore underreporting amongst young adults in Greater Jakarta. We use the 2010 Greater Jakarta Transition to Adulthood Survey (GJTAS), a survey of more than 3000 people aged 20–34 years, to derive estimates of underreporting based on discrepancies reported in the timing of marriage, first child birth and first sexual intercourse and sexual activities. Survival and life table analyses are utilised to identify individual and societal predictors of premarital sex and its reporting and to estimate cumulative incidence across young adulthood. The results reveal substantial evidence of underreporting, particularly amongst women, arising from premarital pregnancies. We estimate that the proportion of the female cohort who will engage in premarital sex by the age of 35 years increases from 4.4 to 22% after taking into account evidence of underreporting. Premarital pregnancies and unreported premarital sex is found to be particularly common amongst lower educated people. This raises important questions for policy and research in terms of the provision of information and support for young couples and the methodological implications of substantial underreporting.